Comparison Between Trichoscopic and Histopathological Evaluations of Hair Parameters - Hu D; Tu P; Yang S (Dove Medical Press, 2022)
Danchen Hu,1- 4 Ping Tu,1- 4 Shuxia Yang1- 4 1Department of Dermatology, Peking University First Hospital, Beijing, 100034, People's Republic of China; 2National Clinical Research Center for Skin and Immune Diseases, Beijing, 100034, People's Republic of China; 3Beijing Key Laboratory of Molecular Diagnosis on Dermatoses, Beijing, 100034, People's Republic of China; 4NMPA Key Laboratory for Quality Control and Evaluation of Cosmetics, Beijing, 100034, People's Republic of ChinaCorrespondence: Shuxia Yang, Department of Dermatology, Peking University First Hospital, Beijing, 100034, People's Republic of China, Tel + 86-13661345723, Email yangshuxia@bjmu.edu.cnBackground: Collecting data on hair counts helps dermatologists diagnose hair diseases more accurately. Quantitative trichoscopy analysis and pathologic examination are two common ways to evaluate hair parameters.Purpose: The study aims to compare the effect of quantitative trichoscopy analysis and pathologic examination in hair counting and quantify the hair density of average Chinese people.Methods: Trichoscopy was performed in four scalp regions with a total of twenty-three volunteers without alopecia: frontal, vertex, occipital, and parietal. Hair density parameters were recorded. A 4-mm punch biopsy was performed in the occipital area, and all specimens were transversely sectioned serially and observed to calculate the hair densities.Results: The average hair density, hairs per follicle unit, and vellus hair ratio from quantitative trichoscopy analysis in the occipital region were 163.07± 28.17/cm2, 1.87± 0.25 and 6.60± 3.95%, lower than those from biopsy significantly (214.97± 48.73/cm2, 2.24± 0.30 and 10.48± 6.43%). The hair shaft diameter measured by quantitative trichoscopy analysis was 74.52± 8.02μm, higher than that by histopathologic examination (68.65± 8.00μm) (p< 0.05).Conclusion: Quantitative trichoscopy is a noninvasive, quick, and convenient way to evaluate hair density. Histopathologic examination is an invasive way but provides more accurate data. The data obtained from trichoscopy and pathological examination are different to some extent, which cannot be substituted entirely for each other. This study established the reference for hair density in the adult Chinese population.Keywords: hair, trichoscopy, histopathology